A novel de novo TBX5 mutation in a patient with Holt–Oram syndrome leading to a dramatically reduced biological function. Issue 5 (14th July 2016) - Dreßen, Martina; Lahm, Harald; Lahm, Armin; Wolf, Klaudia; Doppler, Stefanie; Deutsch, Marcus‐André; Cleuziou, Julie; Pabst von Ohain, Jelena; Schön, Patric; Ewert, Peter; Malcic, Ivan; Lange, Rüdiger; et al.
Abstract: Background: The Holt–Oram syndrome (HOS) is an autosomal dominant disorder affecting 1/100.000 live births. It is defined by upper limb anomalies and congenital heart defects with variable severity. We describe a dramatic phenotype of a male, 15‐month‐old patient being investigated for strict diagnostic criteria of HOS. Methods and results: Genetic analysis revealed a so far unpublished TBX5 mutation, which occurs de novo in the patient with healthy parents. TBX5 belongs to the large family of T‐box transcription factors playing major roles in morphogenesis and cell‐type specification. The mutation located in the DNA‐binding domain at position 920 (C→A) leads to an amino acid change at position 85 (proline → threonine). Three‐dimensional analysis of the protein structure predicted a cis to trans change in the respective peptide bond, thereby probably provoking major conformational and functional alterations of the protein. The p.Pro85Thr mutation showed a dramatically reduced activation (97%) of the NPPA promoter in luciferase assays and failed to induce NPPA expression in HEK 293 cells compared to wild‐type TBX5 protein. The mutation did not interfere with the nuclear localization of the protein. Conclusion: These results suggest that the dramatic functional alteration of the p.Pro85Thr mutation leads to the distinctive phenotype of the patient. Abstract : We have identified a so far unpublished TBX5 mutation which occurs de novo in the patient diagnosed for HOS with healthy parents. The mutation is located in a highly conserved region of TBX5 and is predicted to be damaging. Functional experiments confirmed a dramatically reduced biological activity of the mutated TBX5 protein.